Unlocking the potential of farmer-led irrigation development in central and northern Nigeria: What does it take? - Xie, Hua; Schmitter, Petra S.; Obayelu, A. E.; Kato, Edward; Balana, Bedru; Ringler, Claudia (International Food Policy Research Institute, 2023)
The potential for profitable groundwater irrigated area development in Nigeria is 5.04 million hectares (ha), almost all of it located in the country’s central and northern states. To develop this vast area, granular water budgets, financial service provision and support to grow sustainability of production will be needed. Increasing temperature, erratic rainfall, and other extreme events, such as floods and droughts, pose severe threats to development in Nigeria, and particularly in central and northern Nigeria where rainfall is limited, natural resources are threatened by degradation and agriculture, including livestock production, is the major economic driver. Climate change has significant adverse impacts on agricultural production and livelihoods, making the regions’ poor and disadvantaged people even more vulnerable. Agricultural productivity is already affected by climate extreme events and further land expansion would increase degradation and deforestation. At the same time, the central and northern regions of the country are blessed with substantial underground water resources that have been barely tapped. At this point, the potential of farmer-led irrigation, a system where farmers acquire the irrigation technology and access to a water source themselves, is barely exploited. What role could farmer-led, small-scale irrigation play in growing agricultural productivity, rural employment and incomes, and reducing climate stress? And what mechanisms are needed to make this happen?